Evolução da percepção das vogais anteriores /I/ e /i/ e posteriores /U/ e /u/ por acadêmicos do curso de Letras português – inglês da UTFPR - Torres, Marília Camponogara (2012)
Nowadays, English is seen as an international language, that is, it focuses on communication between non-native speakers. In this sense, intelligibility is a basic concept. Starting from this, Flege (1995) asserts that during second language acquisition, students perceive sounds of the L2 as new or similar sounds, systematizing them, respectively, into new or existing categories in the L1. Based on this statement and on the Lingua Franca Core (Jenkins, 2000), this study aims to determine how the perception of the distinction between front vowels /I-i/ and back vowels /U-u/ evolve in the interlanguage of Brazilian learners of English. Specific subjects were those enrolled in Basic English and those who have already studied Advanced English in Letras Português – Inglês at UTFPR, campus Curitiba. In order to test participants‟ perception of these vowels, two tests were created: discriminatory and simple identification tests, based on the classification of Beddor & Gottfried (1995). The first perception test of both groups of participants showed a similar performance to distinguish between different sounds. However, the second showed an increasing percentage in the rates of correct categorization of the back vowels, especially the vowel /u/, while in the front vowels, the perception remained mostly constant for both levels.